Siblings and the Coming-Out Process: A Comparative Case Study. Issue 4 (21st March 2018) - Haxhe, Stephanie; Cerezo, Alison; Bergfeld, Jeannette; Walloch, Joseph C.
ABSTRACT: Siblings play a key, supportive role in the lives of many lesbian and gay adults. Yet siblings are rarely considered in the literature regarding the coming-out process (D'Augelli et al., 1998; Hilton & Szymanski, 2011; LaSala, 2010; Savin-Williams & Dubé, 1998). To fill this gap in the research literature, we carried out a comparative case study in the country of Belgium between two sets of siblings—three Romani brothers with one sibling identifying as a gay male and three White sisters with one sibling identifying as a lesbian. These two cases were pulled from a larger qualitative study (Haxhe & D'Amore, 2014) of 102 native French-speaking Belgian participants. Findings of the present study revealed that siblings offered critical socio-emotional support in the coming out of their lesbian and gay sibling, particularly with disclosing to parents and with fostering self-acceptance.